Distributed Solar Generation for Voltage Improvement and Loss Reduction in a 20 kV Network - Rian Nurdiansyah; Linda Faridah; Muhammad Waliyyuddin Annur; Sutisna; Nurwijayanti Kn (Journal of Renewable Energy and Smart Device, 2026)
Distributed photovoltaic (PV) generation has emerged as a key solution for enhancing the performance of medium-voltage (MV) distribution networks, particularly in isolated systems with limited conventional generation. This study investigates the impact of centralized and distributed PV integration on voltage profile and power losses in the 20 kV East Sumba distribution system. A steady-state load flow analysis using the Newton–Raphson method was performed in DIgSILENT PowerFactory under three PV penetration levels (20%, 50%, and 100% of peak load). The base-case condition shows significant undervoltage at remote buses and total active power losses of 474.47 kW, mainly due to long radial feeders and concentrated loading. The results indicate that centralized PV placement yields the strongest voltage recovery near the interconnection point at 100% penetration, whereas the minimum system power loss is achieved at 50% penetration. By contrast, distributed PV placement provides more uniform voltage support across remote buses, although with lower effectiveness in reducing total system losses. These findings reveal a clear operational trade-off between voltage improvement and loss minimization, implying that the preferred PV placement strategy should be selected according to the specific technical objective of the network. This study provides practical insights for planning and optimizing PV integration in weak and isolated MV distribution systems.